A novel method for designing carbon nanostructures: Tailoring-induced self-scrolling of graphene flakes. (August 2015) - Li, Wen; Zheng, Xin; Liu, Bing; Sun, Xiaoli; Wang, Tao; Zhang, Jun; Yan, Youguo
Abstract: Design and fabrication of functional carbon nanostructures is a challenging but meaningful mission for scientists to propel the development of nanotechnology, such as nanopharmacology, nanobiology and nanofluidic manipulation. In order to fabricate the carbon nanostructures, using forced-field-based molecular dynamics simulations, we proposed a feasible method to obtain the carbon nanostructures through tailoring-induced self-scrolling of graphene flakes. And the shapes of the carbon nanostructures could be regulated by controlling the tailoring patterns. We also analyzed the mechanism for the tailoring-induced self-scrolling of graphene flakes. By analyzing the scrolling process in detail, it was found that the van der Waals interactions were responsible for the formation of the carbon nanostructures. In addition, we also found that the tailoring could also induce the scrolling of Boron Nitride flakes, and this indicates that the tailoring might provide an universal method for self-assembly of two dimensional materials. This work is expected to trigger further studies on the design of nanostructures and the applications of these nanostructures in functional nanodevices.